Feminist emergence in a traditionally male industry: Case from Jordan. The Jordanian banking industry - Niveen M. AlSayyed; Julian Randall (Administrative Sciences, 2023)
Purpose: This research explored the role of female managers as change agents and the "problem of making women visible," specifically in top management positions in in Jordanian banking industry. Methods: This research design is built on the basis of qualitative research, analyzing the perceptions in the mind of research subjects. Interviews were conducted with 32 participants from the Jordanian banking industry. Findings: Our research has revealed different and important insights into the changing role of Jordanian female workers, not only in such a male-dominant industry but also more broadly in Jordan's wider society, in which the Arab masculine culture has been dominant. The positive impact of increased acceptance of females' roles is significantly evident in our research, and we support the assertion that women can survive and prosper in the face of Arab or Eastern culture traditions. In addition, we asserted that females' managers are deemed to be internal change agents through their knowledge, experience, and leadership traits and behavior. Conclusions: We shed the light on emancipation, in which females have had the opportunity to cross previous social and taken-for-granted boundaries, and which has eroded gender-biased boundaries and behavior as a response to the situational demands.
Keywords: 350; change agency; emancipation; female change agents; gendering presumptions; women empowerment